“Working with little:” Access to market infrastructure and its effect on food handling and food safety among vegetable traders in an African city - Kushitor Sandra Boatemaa; Badu Mercy; Kushitor Komla Mawuli; Currie Paul (frontier, 2023)
This article is published by frontier and is also available at https://doi.org/10.3389/fsufs.2022.724190